Ośrodki Idealnie-Plastyczne pod Działaniem Obciążeń Wieloparametrowych - Telega, J.J. (Engineering Transactions, 1972)
The paper represents an attempt of generalization of the theorems given by P. G. Hodge [2] to 1) an infinite family of loadings, 2) the media with non-associated law of plastic flow, 3) the problems of shake-down in the case of incremental collapse.